Paediatric liver re‐transplantation after primary partial liver graft transplantation: a report of four cases. (20th May 2016) - Qu, W.; Zhu, Z.; Wei, L.; Sun, L.; Liu, Y.; Zeng, Z.
Summary: Objective: To discuss rules of anatomic shifting of the porta hepatis structures of the original graft and dissection techniques for the portal vein (pull‐out technique) in pediatric liver re‐transplantation. Method: We summarized four cases of paediatric liver re‐transplantation. The main donor type is partial liver graft especially using the left lateral lobe. Result: In paediatric liver re‐transplantation, gross morphological changes were observed in the liver, and the spatial position of the porta hepatis structures was shifted clockwise (with the anastomosis of the hepatic vein as the origin). Preoperative three‐dimensional imaging showed that segment 3 of the liver graft increased in a compensatory manner. The pull‐out technique could expose the surgical field without dissection and separation, and reduce the technical difficulty of identifying and dissociating the anatomical structures. Conclusion: Changes in the spatial location and structure of the liver portal anatomy increase the difficulties and risks of surgery. We can reduce the difficulty of surgical anatomy, and the risk of bleeding and injury and increase the safety of paediatric liver re‐transplantation by evaluation and the application of special techniques.